2017
DOI: 10.1002/slct.201700203
|View full text |Cite
|
Sign up to set email alerts
|

Highly Acidic, Thermal Stable NbPO4@Fullerene Catalyst for Dehydration of Cyclohexanol

Abstract: A highly acidic fullerene containing niobium phosphate catalyst demonstrating high thermal stability is synthesized by one pot Sol‐Gel EISA method. The ratio of niobium, phosphorous and surfactant plays a key role for the in‐situ fullerene generation. A thorough study of elemental, textural and chemical properties using different experimental techniques and an extensive catalytic investigation has been done using a series of catalysts synthesized by varying different parameters. The high conversion and selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Thus, the absolute C2 configuration for compounds 27-30 was determined to be: (2R) for 27, (2S) for 28, (2S) for 29 and (2R) for 30. Finally, the authors observed that the conjugation of epiandrosterone derivatives with C60 increases the solubility of these new hybrid systems (27)(28)(29)(30) in organic solvents such as chloroform, dichloromethane and dimethylformamide, among others. It is therefore undeniable that the presence of the steroid unit in the new hybrid compounds (27, 28, 29 and 30) improves their solubility.…”
Section: Scheme 5 Synthesis Of Steroid-fullerene Hybrid 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the absolute C2 configuration for compounds 27-30 was determined to be: (2R) for 27, (2S) for 28, (2S) for 29 and (2R) for 30. Finally, the authors observed that the conjugation of epiandrosterone derivatives with C60 increases the solubility of these new hybrid systems (27)(28)(29)(30) in organic solvents such as chloroform, dichloromethane and dimethylformamide, among others. It is therefore undeniable that the presence of the steroid unit in the new hybrid compounds (27, 28, 29 and 30) improves their solubility.…”
Section: Scheme 5 Synthesis Of Steroid-fullerene Hybrid 21mentioning
confidence: 99%
“…These compounds have unique optical, [7][8][9] electrophysical, [10][11][12] mechanical, [13][14][15] tribological, [16][17][18] sorption [19][20][21][22] and biological [23][24][25] properties. New dyes and catalysts [26][27][28][29][30] have even been discovered among functionalized fullerenes. The use of functionalized fullerenes in the field of medical chemistry, in particular for the treatment of significant diseases, seems interesting because of their wide range of biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…The catalysts were synthesized by evaporation induced self-assembly (EISA) process as described earlier. [9,48,49] First, at room temperature, ethanol was used to dissolve CTAB. Then MoCl 5 was slowly added and stirred for 1 h followed by addition H 3 PO 4 dropwise.…”
Section: Catalyst Synthesismentioning
confidence: 99%
“…They are being successfully studied in areas such as medicine [20][21][22][23][24], solar energy [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], and technology [40][41][42][43][44][45]. Compounds possessing unique [46][47][48], electrophysical [49][50][51], mechanical [52][53][54], tribological [55][56][57], sorption [58][59][60][61], and biological properties [62][63][64] and even new dyes and catalysts [65][66][67][68][69] have already been found among fu...…”
Section: Study Of Geometric Parameters and Electrochemical Properties...mentioning
confidence: 99%
“…Reprinted (adapted) with permission from Reference [173]. Copyright 2013 American Chemical Society 80,68) are none other than adducts on [6,6] type bonds near the pentalene unit. The energy difference between the first set of monoadducts and the other possible regioisomers is larger than 11 kcal × mol −1 [173].…”
Section: Bingel's Reactionmentioning
confidence: 99%